Healthcare Utilization, Legal Incidents, and Victimization Following Traumatic Brain Injury in Homeless and Vulnerably Housed Individuals: A Prospective Cohort Study. Issue 4 (July 2015) - To, Matthew J.; O'Brien, Kristen; Palepu, Anita; Hubley, Anita M.; Farrell, Susan; Aubry, Tim; Gogosis, Evie; Muckle, Wendy; Hwang, Stephen W.
Abstract : Objective: To characterize the associations between a history of traumatic brain injury (TBI) and subsequent healthcare utilization, legal involvement, and victimization. Setting: Three major Canadian cities. Participants: A total of 1181 homeless and vulnerably housed adults who were single and 18 years or older. Data for 968 participants (82%) were available at 1-year follow-up. Design: Prospective cohort study. Data were collected using structured, in-person interviews at baseline in 2009 and approximately 1 year after baseline. Main Measures: Self-reported TBI, 12-item Short Form Health Survey, healthcare, and criminal justice use questionnaires. Results: The lifetime prevalence of TBI was 61%. A history of TBI was independently associated with emergency department (ED) use [adjusted odds ratio (AOR) = 1.5, 95% confidence interval (CI): 1.11–1.96], being arrested or incarcerated (AOR = 1.79, 95% CI: 1.3–2.48) and being a victim of physical assault (AOR = 2.81, 95% CI: 1.96–4.03) during the 1-year follow-up period. Conclusions: Homeless and vulnerably housed individuals with a lifetime history of TBI are more likely to be ED users, arrested or incarcerated, and victims of physical assault over a 1-year follow-up period even after adjustment for health status and other confounders. These findings have public health and criminal justice implications and highlight the need for effective screening, treatment, and rehabilitation for TBI in this population.